SEASONAL VARIATION AND ABUNDANCE, RESIDENTIAL AND IUCN STATUS OF AVIAN DIVERSITY IN FOREST COMMUNITY IN JASHPUR DISTRICT (C.G.) - Tirkey, Jyoti; Sahu, K. R.; Pandey, Pratibha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Birds are one of the most important units in the food chain on this planet. They play significant role in the environment. They are good indicators for understanding climate changing in the ecosystems. Birds attract peoples due to their fascinating colors, courtship behavior, sound and their beauty. The present study was carried out in Forest Community in Jashpur District (C.G.) between January to December 2021 with the objectives to explore the bird diversity and seasonal variation along with the factors affecting bird diversity in the study area. Mackinnon’s Listing Method and Point Count Method were used for bird survey during winter and summer seasons. In the present study, attempt has been made to collect the relevant information regarding the avian fauna of around the study site Jashpur (C.G.). The periodic survey of the study area, showed great deal of avian biodiversity. During the study period, a total of 102 bird species during the two year periods belonging to 15 orders and 39 families were reported were recorded. Various bird species recorded during the whole period of study in “Forest area near Sarudih tea garden area (Site A), nearly village Gamharia (Site B) and near Neemgoan dam (Site-C) Jashpur (C.G.).” were given the IUCN status (Table 5.9) so that the conservational measures could be suggested/adopted accordingly. A comparison of the recorded avian species was made with the recent Red Data List published by IUCN. Accordingly, these bird species were categorized into two IUCN categories, namely, Least Concern (LC) and Endangered (EN). According to Red Data Book of IUCN 102, “Globally threatened” species were also recorded from the study area. Out of 100 globally threatened species, and only 2 species was in endangered category.